Has Regional Integration Led to Greater Risk-Sharing in Asia? - Thiam Hee Ng; Damaris Lee Yarcia (Asian Development Bank (ADB), 2014)
The 1997–1998 Asian financial crisis revealed the latent risks present in an increasingly integrated global economy and how virulent these risks can be when roused from dormancy. Given the inevitability of integration, the challenge is how to maximize its benefits while minimizing its costs. One benefit of greater integration, particularly financial integration, is that countries can diversify their risks, thus allowing them to smooth out their consumption. This paper analyzes whether the degree of risk-sharing in East Asia has improved along with the observed rise in integration in the region. Higher risk-sharing is expected to result in (i) higher intraregional correlation of consumption across time and relative to output, and (ii) a higher residual in the panel regression of consumption on output. The results show that risk-sharing continues to be low in Asia. The increase in cross-economy correlation in consumption coincided with an even higher cross-economy correlation in output. Furthermore, the correlation between domestic consumption and domestic output growth remains high. And finally, correlation within the region is lower than correlation with the global economy. These findings suggest that higher consumption correlation is the result of stronger economic ties rather than greater risk-sharing.
hdl:11540/1288
Keywords: F36; F51; F65; 330; risk-sharing; ASEAN; integration